Effects of Vocabulary Instructional Strategies on related Achievement in Biology in Secondary School Students - Gafoor K, Abdul Gafoor; Maloof, Farhan; T K, Dhanya (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
This study premise that words are fundamentally conceptual, that science and literacy share a core of set of meaning making strategies, that text can play a set of dynamic roles in inquiry processes and the related science learning outcomes. This paper reports the effects of graphic self-instructional material on vocabulary in four broad areas of biology in class X (SCERT, Kerala), direct vocabulary instruction and collaborative self- learning of vocabulary in the unit Movement and locomotion of class XII biology (NCERT). The vocabulary instruction intervention was preceded by content analysis of respective textbooks that resulted in listing of 250 terms from class X and 1351 terms from class XII text books. Based on morphological analysis the terms from class X biology were incorporated into a graphic self-instructional material for students to learn these terms. Larger list of terms from class XII were reduced into 420 words which were then rated for difficulty by undergraduate biology students and accordingly units with higher number of difficult terms were identified. The vocabulary in the unit with maximum and most difficult terms, Movements and locomotion, were incorporated into a vocabulary instructional intervention, which were administered either through direct instruction or through collaborative self-learning. The vocabulary instruction, of less than a few class periods, could enhance achievement of vocabulary allied concepts among both class x and xii students, over and above the equivalent control groups who had completed regular biology instruction and learning in these units. These effects were all very large, except in one intervention where the effect size was yet large.